2009
DOI: 10.1111/j.1750-3841.2009.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone Treatment on Botrytis cinerea and Sclerotinia sclerotiorum in Relation to Horticultural Product Quality

Abstract: Botrytis cinerea and Sclerotinia sclerotiorum are fungal pathogens that cause the decay of many fruits and vegetables. Ozone may be used as an antimicrobial agent to control the decay. The effect of gaseous ozone on spore viability of B. cinerea and mycelial growth of B. cinerea and S. sclerotiorum were investigated. Spore viability of B. cinerea was reduced by over 99.5% (P < 0.01) and height of the aerial mycelium was reduced from 4.7 mm in the control to less than 1 mm after exposure to 450 or 600 ppb ozone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 26 publications
0
36
0
2
Order By: Relevance
“…Increasing pressure in the food conservation field to replace chemical-based applications has urged researchers to focus on studying new reliable and healthy strategies of extending the postharvest and shelf life of produces (Tharanathan 2003). Previously, a number of materials were tested for their preservative potentials and appropriateness to organic consumption during storage of produces, such as ethanol (Karabulut et al 2004;Lichter et al 2002;Sabir et al 2006), mineral oils (Valero et al 2006), chlorinated or hot water (Del Nobile et al 2008), ethephon (Jayasena and Cameron 2009), chitosan (a natural polysaccharide) (Romanazzi et al 2009), and ozone (Sharpe et al 2009). In these endeavors, undesirable odors or bitterness that may confer to the produces during storage have been significant limitations in practical applications of such materials (Soliva-Fortuny and Martín-Belloso 2003;Mishra et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing pressure in the food conservation field to replace chemical-based applications has urged researchers to focus on studying new reliable and healthy strategies of extending the postharvest and shelf life of produces (Tharanathan 2003). Previously, a number of materials were tested for their preservative potentials and appropriateness to organic consumption during storage of produces, such as ethanol (Karabulut et al 2004;Lichter et al 2002;Sabir et al 2006), mineral oils (Valero et al 2006), chlorinated or hot water (Del Nobile et al 2008), ethephon (Jayasena and Cameron 2009), chitosan (a natural polysaccharide) (Romanazzi et al 2009), and ozone (Sharpe et al 2009). In these endeavors, undesirable odors or bitterness that may confer to the produces during storage have been significant limitations in practical applications of such materials (Soliva-Fortuny and Martín-Belloso 2003;Mishra et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Foi observada oscilação diária dos dados de variação de cor, o que pode ter ocorrido devido ao fato de a podridão-mole apresentar lesões pontuais e a amostragem ser aleatória. Semelhantemente, Sharpe et al (2009) Durante o armazenamento de produtos agrícolas, pode ocorrer degradação de reservas de carboidratos, em que o amido é hidrolisado a sacarose e esta, por sua vez, em açúcares redutores, liberando dióxido de carbono e água (BHERING et al, 2009). Esse processo respiratório pode, portanto, alterar o teor de açúcares, em batatas armazenadas.…”
Section: Figura 4 Estimativa Dos Açúcares Solúveis Totais (A) Açúcaunclassified
“…Alwi and Ali have shown that ozone was more effective in reducing microbial populations of Listeria monocytogenes and E. coli O157 than Salmonella enterica on fresh‐cut bell peppers, and suggested that higher resistance of S. enterica could be associated with higher density of its cell membrane due to higher content of phospholipid components . Similarly, Sclerotinia sclerotiorum was found to be more resistant to ozone exposure than B. cinerea , and Colletotrichum coccodes more resistant than Alternaria alternata on artificially inoculated carrots and tomato fruit, respectively. In this context, continuous exposure to ozone at 0.3 µmol mol −1 significantly reduced disease severity and decay in peaches inoculated with Monilinia fructicola , while having no effect on decay in fruit inoculated with B. cinerea , Mucor piriformis or Penicillium expansum .…”
Section: Practical Use Of Ozonementioning
confidence: 99%
“…It has been demonstrated in a number of studies that exposure to ozone reduces the production of spores in many fungi, e.g. in B. cinerea exposed to ozone at 0.45 and 0.6 µmol mol −1 for 48 h, in B. cinerea , M. fructicola , M. piriformis , P. expansum wound‐inoculated on peaches, and B. cinerea inoculated on kiwi fruit when continuously exposed to ozone at 0.3 µmol mol −1 . When the produce is removed from the ozone‐enriched atmosphere, however, the production of spores often resumes.…”
Section: Practical Use Of Ozonementioning
confidence: 99%